Schwannoma of the Recurrent Laryngeal Nerve: A Rare Entity. Issue 1 (January 2017) - de Heer, Linda M.; van Berkhout, Ferdinand Teding; Priesterbach-Ackley, Loudy P.; Buijsrogge, Marc P.
Neurogenic tumors are the most common posterior mediastinal tumors in adults. Schwannomas originating from the recurrent laryngeal nerve are rare. The present study describes a 46-year-old man with a tumor in the left superior mediastinum. Because of the narrow relationship with the aorta and the left pulmonary artery, the tumor was excised by left-sided minithoracotomy. The tumor, a schwannoma, originated from and encased the left recurrent laryngeal nerve. Six months after surgery, the patient was free of recurrence without symptoms other than hoarseness. "Additional imaging by magnetic resonance imaging could raise the probability of a neurogenic origin of the mass, eventually leading to collaboration with the neurosurgeon in this case."